Nazirites in late Second Temple Judaism : a survey of ancient Jewish writings, the New Testament, archaeological evidence, and other writings from late antiquity - Chepey, Stuart Douglas, 1970- (Ancient Judaism and Early Christianity, 2005)
Nazirites appear in a number of sources relevant to Judaism of the late Second Temple period. This book surveys the pertinent evidence and assesses what it reveals regarding the role of the Nazirite within Judaism of the late Second Temple and early Christian era. The survey is arranged according to three primary sections: "Direct Evidence for Nazirites"; "Possible and Tangential Evidence for Nazirites"; and a final section, "Making Sense of the Evidence." It concludes by arguing that the role of the Nazirite portrayed in sources was that of a religious devotee, and concomitant with biblical law, Nazirite devotion typically involved flexibility, personal freedom of expression, and adaptation to outside cultural norms. Those interested in the Nazirite vow as portrayed in the New Testament and other relevant sources will find this study useful, as will those interested in Bible translation and interpretation in late Second Temple and early rabbinic literature.